2022
DOI: 10.1029/2022gb007469
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Change Affects Soil Organic Carbon Mineralization and Greenhouse Gas Production in Coastal Wetlands

Abstract: Plant invasion and aquaculture activities have drastically modified the landscape of coastal wetlands in many countries, but their impacts on soil organic carbon (SOC) mineralization and greenhouse gas production remain poorly understood. We measured SOC mineralization rate and soil CO2 and CH4 production rates in three habitat types from 21 coastal sites across the tropical and subtropical zones in China: native mudflats (MFs), Spartina alterniflora marshes (SAs), and aquaculture ponds (APs). Landscape change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 74 publications
2
13
1
Order By: Relevance
“…Earlier studies showed that landscape transformation may impact the organic and inorganic pools of the soil differently, and that the soil greenhouse gas production and emission may respond in an unexpected way. For example, invasion of mudflats by S. alterniflora has been shown to increase soil organic carbon concentration but decrease inorganic carbon concentration, whereas subsequent removal of S. alterniflora to create aquaculture ponds caused the opposite changes (Duan et al, 2023;Yang et al, 2022a;Hong et al, 2023). Similar changes were also observed in soil organic carbon mineralization rate (Yang et al, 2022a;Hong et al, 2023).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Earlier studies showed that landscape transformation may impact the organic and inorganic pools of the soil differently, and that the soil greenhouse gas production and emission may respond in an unexpected way. For example, invasion of mudflats by S. alterniflora has been shown to increase soil organic carbon concentration but decrease inorganic carbon concentration, whereas subsequent removal of S. alterniflora to create aquaculture ponds caused the opposite changes (Duan et al, 2023;Yang et al, 2022a;Hong et al, 2023). Similar changes were also observed in soil organic carbon mineralization rate (Yang et al, 2022a;Hong et al, 2023).…”
Section: Introductionmentioning
confidence: 92%
“…For example, invasion of mudflats by S. alterniflora has been shown to increase soil organic carbon concentration but decrease inorganic carbon concentration, whereas subsequent removal of S. alterniflora to create aquaculture ponds caused the opposite changes (Duan et al, 2023;Yang et al, 2022a;Hong et al, 2023). Similar changes were also observed in soil organic carbon mineralization rate (Yang et al, 2022a;Hong et al, 2023).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations